Single nucleus RNA sequencing of the cerebral cortex from genetically diverse inbred mouse strains reveals differences in pericyte and endothelial cell composition - Jieun Park; Bonnie Taylor-Blake; James L. Krantz; Mark J. Zylka (PLoS ONE, 2025)
Genetic background influences animal behavior and susceptibility to brain diseases. To evaluate how genetic background influences the relative number and/or types of cells in the brain, we performed single nucleus RNA sequencing (snRNAseq) on fourteen genetically distinct collaborative cross (CC) inbred mouse strains. These data comprise over 287,000 nuclei derived from 92 samples across the strains. We identified 12 principal cell types and 60 refined cell types in each of the strains. Pericytes and endothelial cells were the two principal cell types to show a statistically significant difference in cell proportion between strains. We validated these findings histologically by staining for pericyte (CD13) and endothelial cell (PECAM-1) markers. Consistent with our snRNAseq analyses, we histologically observed differences in pericyte and endothelial cell counts between strains. In addition, we found that the proportion of certain subsets of excitatory and inhibitory neurons varied in some strains. Overall, our study suggests that genetic background can influence brain cell type composition, with a notable influence on cells that make up the neurovascular unit.